ANALISIS FAKTOR PENENTU KEPUTUSAN MASYARAKAT MEMBELI PAKAIAN BEKAS SECARA ONLINE DAN OFFLINE DI KOTA TIMIKA - Oktariani Ambo; Antje Tuasela (CV. Adiba Aisha Amira, 2025)
This study aims to determine what factors determine people's decisions in buying used clothes online and offline in Timika City. This study uses a descriptive method. In this study, the data collection techniques used are interviews, observations, questionnaires, and documentation. To find out what factors determine people's decisions, the data analysis instrument used is factor analysis. The results of this study indicate that the determining factors for people's decisions to buy used clothes online in Timika City are influenced by factors of service quality, ease of transactions, satisfaction with products, and cost efficiency. Meanwhile, people's decisions to buy used clothes offline in Timika City are influenced by factors of service quality, price assessment, trust, and security.